Adenosine/A2B receptor signaling ameliorates the effects of aging and counteracts obesity - Gnad, Thorsten; Navarro, Gemma; Lahesmaa, Minna; Reverte-Salisa, Laia; Copperi, Francesca; Cordomi, Arnau; Naumann, Jennifer; Hochhäuser, Aileen; Haufs-Brusberg, Saskia; Wenzel, Daniela; Suhr, Frank; Jespersen, Naja Zenius; et al. (Cell metabolism, 2020)
The combination of aging populations with the obesity pandemic results in an alarming rise in non-communicable diseases. Here, we show that the enigmatic adenosine A2B receptor (A2B) is abundantly expressed in skeletal muscle (SKM) as well as brown adipose tissue (BAT) and might be targeted to counteract age-related muscle atrophy (sarcopenia) as well as obesity. Mice with SKM-specific deletion of A2B exhibited sarcopenia, diminished muscle strength, and reduced energy expenditure (EE), whereas pharmacological A2B activation counteracted these processes. Adipose tissue-specific ablation of A2B exacerbated age-related processes and reduced BAT EE, whereas A2B stimulation ameliorated obesity. In humans, A2B expression correlated with EE in SKM, BAT activity, and abundance of thermogenic adipocytes in white fat. Moreover, A2B agonist treatment increased EE from human adipocytes, myocytes, and muscle explants. Mechanistically, A2B forms heterodimers required for adenosine signaling. Overall, adenosine/A2B signaling links muscle and BAT and has both anti-aging and anti-obesity potential.